MODEL EDUKASI PENERAPAN IPTEKS & KETERAMPILAN RAMUAN PEPAYA SEBAGAI ANTHELMINTIK PADA AYAM - Argus, Argus; Jamaluddin, Jamaluddin; Khoirulloh, Khoirulloh; Firdausi, Nilam; Tanwil, Tanwil (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
This PKM-M aims to implement the education of applying science and technology & the ability of ingredients of beneficial papaya. To know the society response in the education of applying science and technology & the ability of ingredients of beneficial papaya as anthelmintik to minimalize the wormy in the livestock chicken. To manage the continuative enterprise program in Kambingan village. The action of PKM-M is based on the following statements of the problem: 1) Implementing Papaya Ingredients by illuminating and adjoining. The illumination was attended by public figure, breeder, and public apparatus. In the illumination, the interactive discussion happened between the participants, and the informant and PKM-M team. Discussion aboutÂ chicken diseases. Ascaridia galli is a parasitic gilig worm which is mostly found in the chicken and causes a big loss of financial for breeder fowl. The usage of natural ingredient is much better than chemical ingredient. One of the efforts in controlling an environmentally safe parasite is taking the advantages of the trash of papaya plants.Adjoining was done by helping (training) the breeder society in the case of giving the liquid drop to Papaya Ingredients, 2) the society responses to the importance of the advantage of Carica papaya trash, there was an improvement of society understanding after joining this program, 3) the continuative effortwas done by adjoining while training and working together in the future.Â The continuative effort would be realized in PKM-K or IbW (science and technology for society) in this year, in which the object is Kambingan village.Â Keywords: Carica papaya trash, anthelmintik, Ascaridia galli, breeder society